Combined spinal epidural analgesia in labor: comparison of intrathecal 2mg plain bupiv a caine versus heavy bupiv a caine with fentanyl - Ahmad Nizam, Ismail (2011)
Spinal opioid analgesia utilizing analgesics has been one of the major developments during the past decade in the management of acute and chronic pain. The relief of pain is due to the interaction of the opioid injected epidurally or intrathecally with a specific opioid receptor in the spinal cord. The result is zones of segmental analgesia without the loss of motor function or loss of other sensory modalities such as touch sensation. The use of opiates in the conjunction with the spinal or epidural local anaesthetic such as bupivacaine afford prolonged post operative pain relief (Aboulish et al, 1988, Akerman et al, 1988). A possible synergistic analgesic effect between the local anaesthetic and opioids may have important clinical implications, however, this effect is difficult to evaluate in man (Akerman et al, 1988). As there are only few studies on analgesic duration of plain bupivacaine, a double blind randomized prospective study was conducted on 90 patients who had undergone parturient in labour in Hospital Universiti Sains Malaysia, Kelantan. The aim of our study was to ascertain whether a smaller dose of intrathecal bupivacaine can preserve the quality of analgesia while generating fewer adverse effects. Ninety patients with no complicating obstetric and medical problem, whose age ranges from 18 and 42 years were selected randomly into two groups. Group I patients received 2 mg plain intrathecal bupivacaine with 25mcg fentanyl and group 2 received 2 mg intrathecal heavy bupivacaine with 25 meg fentanyl .The pain was assessed on the variables at time 0 (time at the start of IT injection) and at 5, 15,30 min. The result revealed that the use of 2 mg heavy bupivacaine with 25 meg fentanyl produce adequate level of analgesia at TIO and no incidence of high sensory block. It was statistically significant comparing both groups with a p value of 0.003. In terms of side effect, our study has shown less incidence of side effect including nausea and/or vomiting as well as incidence of pruritus is significantly reduced in the study population ( nausea and/or vomiting P value at 0.049 and pruritus p value = 0.026.